Preservation of glanular cleft in the configuration of a vertical slit neomeatus in modified mathieu hypospadias repair - Khizer Mansoor; Thomas Tsang; Philemon E Okoro (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of this study is to review the results of modified Mathieu's repair in a single surgeon's series. The technique involved preserving the apical part of the glanular cleft including the lips, part of the un-formed glanular meatus in the reconstruction of a vertical slit neomeatus. The achievement of a vertical slit neomeatus was critically assessed. Materials and Methods: A retrospective analysis was carried out for all cases of Mathieu's repair done by a single surgeon over the past 22 years (1995-2017). Inclusion criteria included all cases of coronal, subcoronal and distal penile hypospadias. Cases done as redo secondary Mathieu's procedure were also included irrespective of the type of primary procedure. Results: A total of 97 cases fulfilled the inclusion criteria. 91 patients had a primary Mathieu's procedure. Six patients had a Mathieu's repair as a secondary operation. The complications included 4 fistulas (4.12%), 3 meatal retractions (3.09%) and 2 mild stenosis (2.06%). There were no breakdowns of the repair Ninety-four patients (96.90%) had a glanular vertical slit neomeatus. This included patients with a fistula and both patients with mild stenosis. All fistulas were successfully closed in a single attempt. Four patients (4.12%) had a slight splaying of the lower end of the meatus and three circular neomeatus (3.09%). Both cases of stenosis responded well to dilatation. Conclusion: Mathieu's repair is an old and time-tested technique used in surgery of distal hypospadias. With modification aiming to preserve the apical part of the glanular cleft adopted, a vertical slit neomeatus can be achieved readily as shown by our series and major complications appear rather uncommon.